Biofunctionalization of Silver Nanoparticles With Lactonase Leads to Altered Antimicrobial and Cytotoxic Properties - Gupta, Kshitiz; Chhibber, Sanjay (Frontiers in Molecular Biosciences, 2019)
Background: N-acylated homoserine lactone lactonase cleaves the Acyl homoserine lactone molecules produced by biofilm-forming pathogens and silver nano-particles (AgNPs) are known for antibacterial effect against several gram- positive and gram -negative bacteria. In this study, AgNPs were coated with N-acylated homoserine lactonase protein (AgNPs-AiiA) isolated from Bacillus sp. ZA12. Results: The AgNPs-AiiA complex was characterized by UV-visible spectra, Dynamic light Scattering, Fourier transform infrared spectroscopy (FTIR) and Field Emission Scanning Electron Microscope (Fe SEM). The synthesized nano-particles were found to be spherical in shape and had an approximate size of 22.4 nm. Treatment with AiiA coated AgNPs showed significant reduction in exopolysaccharide production, metabolic activity, cell surface hydrophobicity of bacterial cells, and anti-biofilm activity against multidrug-resistant K. pneumoniae as compared to treatment with AiiA protein and neat AgNPs. AgNPs-AiiA complex exhibited potent antibiofilm activity at sub-optimal concentration of 14.4 µg/mL without being harmful to the macrophages and to the various tissues including kidney, liver, spleen, and lungs of BALB/c mice upon intra-venous administration. Conclusion: It is concluded that at a concentration of 14.4 µg/mL, AgNPs coated with AiiA kill bacteria without harming the host tissue and provides a suitable template to design novel anti-biofilm drug to circumvent the issue of drug resistance.